2001
DOI: 10.1051/0004-6361:20010467
|View full text |Cite
|
Sign up to set email alerts
|

Background galaxies as reddening probes throughout the Magellanic Clouds

Abstract: Abstract.We study the spectral properties in the range 3600Å-6800Å of the nuclear region of galaxies behind the Magellanic Clouds. The radial velocities clarified the nature of the objects as background galaxies or extended objects belonging to the Clouds. For most galaxies behind the main bodies of the LMC and SMC, radial velocities were measured for the first time. In the present sample typical LMC background galaxies are nearby (4000 < V (km s −1 ) < 6000), while SMC's are considerably more distant (10 000 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 36 publications
10
43
0
Order By: Relevance
“…The remainder of the stars should be classified as outliers and need further careful inspection. Dutra et al (2001) find the Milky Way mean reddening in the direction of the LMC to be around 0.06 mag, and the internal LMC reddening to be E(B − V) = 0.05 ± 0.05. A similar result was obtained by Clementini et al (2003).…”
Section: Mean J and K S Magnitudes And Error Analysismentioning
confidence: 81%
See 1 more Smart Citation
“…The remainder of the stars should be classified as outliers and need further careful inspection. Dutra et al (2001) find the Milky Way mean reddening in the direction of the LMC to be around 0.06 mag, and the internal LMC reddening to be E(B − V) = 0.05 ± 0.05. A similar result was obtained by Clementini et al (2003).…”
Section: Mean J and K S Magnitudes And Error Analysismentioning
confidence: 81%
“…Investigations of the LMC extinction, however, show that it is non-uniform and clumpy (see, for example, Udalski et al 2000;Dutra et al 2001;Zaritsky et al 2004). Therefore, it is necessary to calculate individual reddenings for each of the stars in our sample.…”
Section: Mean J and K S Magnitudes And Error Analysismentioning
confidence: 99%
“…SFD found that at high-latitude regions, their dust maps correlate well with maps of H I emission, but deviations are coherent in the sky and are especially conspicuous in regions of saturation of HI emission towards denser clouds and of formation of H 2 in molecular clouds. The SMC is quite transparent, the average foreground and internal reddenings being 0.01 and 0.04, respectively (Dutra et al 2001). The typical …”
Section: Template Matching Methodsmentioning
confidence: 99%
“…were computed by averaging the extinction estimates in the literature (Dutra et al 2001;Oestreicher & Schmidt-Kaler 1996;Oestreicher et al 1995;Massey et al 1995;Schwering & Israel 1991;Bessel 1991;and Capaccioli et al 1990). Extinction values derived from extinction maps of the Magellanic Clouds were weighted twice in our computation.…”
Section: ) the Values For E(b − V)mentioning
confidence: 99%